PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING PADA MATERI GOTONG-ROYONG FASE E KELAS X - Ronaldo Zai (Jurnal Pendidikan Sosial Keberagaman, 2022)
This study aims to determine the application of contextual teaching and learning models in phase E mutual aid material class X. This research uses a literature study method with data analysis techniques using this analysis technique. The conclusion in this study is that the application of the contextual teaching and learning model to the phase E mutual aid material of class X is carried out with the first few stages of the teacher conveying learning outcomes, the two students are divided into several groups, the three students from each group are given the opportunity to ask questions and discuss, the four teachers direct the students to Conduct contextual learning activities with the theme of mutual cooperation, and finally, the teacher conducts evaluations and assessments.